Treatment and prognostic factors of patients with thymic epithelial tumors at first recurrence or progression. (November 2017) - Banna, Giuseppe L; Sheel, Ankur; Sheel, Varun; Bille, Andrea; Routledge, Tom; Fernando, Shalini; Nair, Arjun; Lal, Rohit
Aim: The treatment of patients with recurrent or progressive thymic epithelial tumors remains uncertain due to limited data in this rare disease.Materials & methods: A retrospective 10-year monoinstitutional analysis was conducted on 25 patients with first recurrence or disease progression following primary treatment.Results: Twenty patients had thymoma, five thymic carcinomas. Ten patients (40%) received surgery, four (40%) following chemotherapy; 17 (68%) had chemotherapy, with a combination regimen in 16 of them (94%). Surgery had a significant effect both on overall survival and progression-free survival-2 by univariate analysis (p = 0.04), combination chemotherapy only on progression-free survival-2 (p = 0.03).Conclusion: Combination chemotherapy and surgery at first recurrence/progression of thymic epithelial tumors were associated with improved survival.Discussion: Although several limitations may have affected this retrospective study on a relatively small number of patients with this rare entity of recurrent thymic malignancies, we suggest the use of combination chemotherapy and surgery at their first recurrence may have contributed to the high overall and progression-free survival observed with adequate follow-up and deserve further investigations in broader retrospective and comparative studies.